Direction: Rome - details from a journey from Lisbon to Genoa at the end of the Settecento (Palíndromo, 2022)
During the late 18th century, Rome still dominates the dreams and objectives of European artists. They leave from Paris, London, as well as from cities less studied by canonical art history, such as Lisbon, Madrid, or even Marseille, Barcelona, and Zaragoza. Through the detailed enumeration of his stops from Lisbon to the « Eternal City », Portuguese priest Anastacio de Santa Clara’s terrestrial itinerary allows us to retrace one of these usual but lesser-known itineraries, starting from the Western confines of Europe. Published for the first time in 1791, based on his own personal experience, Santa Clara’s guide allows us to better understand these journeys, in geographic as well as temporal terms. We’ll travel with him to Genoa, where he strongly recommends the traveler to continue his journey to Rome by sea.
Keywords: Travel; 18th century; Spain; France; Italy